UTILIZATION OF TINIRA PLANTS IN SOCIAL, CULTURAL, AND RELIGIOUS EVENTS IN THE WAWONII ISLANDS - Laxmi; Raemon; Jumrana (Media Inovasi Pendidikan dan Publikasi, 2023)
This paper describes the use of the tinira plant in the local language in the Wawonii archipelago, Konawe Regency Islands, in general tinira is known as young rattan which is generally used as a consumption pattern for most people in Indonesia. Tinira is used socially, culturally and religiously so that this traditional food is always a special dish at every event in Wawonii village. In utilizing tinira, the community uses it wisely so that knowledge is needed for group members who will choose tinira that is suitable for consumption. Harmony with nature and the forest is an important part of preserving because traditional tinira food is integrated with event held in Wawonii village such as traditional weddings, events of death and the completion of the Qur’an. The method use in this paper is descriptive qualitative with data collection techniques through in – dept interviews, regular interviews and documentation. Data analysis was carried out by connecting between various categories of data and grouping them based on their purpose, then synergizing and connecting them with various literature and other data so that data was obtained that could be discussed in its entirety and comprehensively. The results showed that tinira had been used for generations and was able to enculturate the people of the Wawonii islands. The use of tinira is able to strengthen the mepokowali collaboration system from the start of preparing for social, cultural and religions events.